Training-induced changes on blood lactate profile and critical velocity in young swmmers - Toubekis, A. G.; Tsami, A. P.; Smilios, I. G.; Douda, H. T.; Tokmakidis, S. P. (The Journal of Strength and Conditioning Research, 2011)
This study examines the efficacy of critical swimming velocity (CV) for training prescription and monitoring the changes induced on aerobic endurance after a period of increased training volume in young swimmers. An experimental group (E: n = 7; age: 13.3 ± 1.3 years), which participated in competitive training was tested at the beginning (W0), the sixth week (W6), and 14th week (W14) to compare the changes of aerobic endurance indexes (CV; lactate threshold [LT]; velocity corresponding to blood lactate concentration of 4 mmol/L: V4). A control group (C: n = 7; age: 14.1 ± 1.6 years), which refrained from competitive training, was used to observe maturation effects and was tested for CV changes between W0 and W14. The average weekly training volume was increased after the sixth week in the E group and was unchanged for the C group. The CV was not different between or within groups at W0 and W14 (p > 0.05). The LT of the E group was no different compared to V4 and CV at W0 and W6 (p > 0.05) but was higher than CV at W14 (p < 0.05). The LT increased (6.5 ± 5.3%, p < 0.05), but V4 and CV were unchanged after W6 (3.6 ± 1.9%; 2.1 ± 1.2%, p > 0.05). LT, V4, and CV were unchanged despite the increased training volume from W6 to W14 (LT: 1.2 ± 4.3%, V4: 0.8 ± 1.5%, CV: 0.3 ± 0.8%; p > 0.05). These findings suggest that CV pace may be effectively used for the improvement of aerobic endurance in young swimmers. The aerobic endurance indexes used for the assessment of swimmers' progression showed different rates of change as a response to the same training stimulus and cannot be used interchangeably for training planning.